Natural polymer-based food packaging material as well as preparation method and application thereof
By ion-exchange reaction between chitosan quaternary ammonium salt and polycustard sodium, natural polymer-based food packaging materials with hydrophobicity and antibacterial properties were prepared, which solved the negative impact of existing plastic packaging materials on the environment and the insufficient food packaging needs, and achieved efficient food preservation and environmental protection goals.
Patent Information
- Application Number
- CN202411982165.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing plastic packaging materials have a great negative impact on the environment and are difficult to meet the antibacterial and water vapor barrier needs of food packaging.
Using chitosan quaternary ammonium salt as raw material, natural polymer-based food packaging materials with good hydrophobicity and antibacterial properties were prepared through ion exchange reaction with sodium polyhydrogenase.
It achieves good antibacterial properties, biocompatibility, mechanical strength and water vapor barrier properties of food packaging materials, extends the shelf life of food and reduces food waste.
Smart Images

Figure CN119798486A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of food packaging materials, and in particular to a natural polymer-based food packaging material and a preparation method and application thereof. Background Art
[0002] Plastic packaging materials have been widely used in the packaging industry due to their lightness, durability, low cost, and excellent protection and sealing properties. Due to the huge amount of plastic packaging used, the demand for raw materials is also increasing, which has aggravated the consumption of natural resources. Therefore, there is an urgent need to develop natural and renewable plastic packaging raw materials.
[0003] Chitosan is widely distributed in nature, and its reserves rank second only to cellulose. It is the second largest natural polymer. The annual biosynthesis of chitosan is about 10 billion tons, which is a recyclable renewable resource. Chitosan quaternary ammonium salt, as an advanced derivative of chitosan, has good antibacterial properties, but due to its good hydrophilicity and excellent water solubility, it is not suitable for use as a food packaging material. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a natural polymer-based food packaging material and a preparation method and application thereof. The natural polymer-based food packaging material provided by the present invention uses chitosan quaternary ammonium salt as a raw material and has good hydrophobicity and antibacterial properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a natural polymer-based food packaging material having a structure shown in Formula 1:
[0007]
[0008] The anion R in formula 1 - Having the structure shown in Formula 2-1 and / or Formula 2-2; in the different structural units of Formula 1, the anion R - Not all of them are structures shown in formula 2-2:
[0009]
[0010] In formula 1, m>0, n>0, m+n=10-600, n / m+n=0.5-0.99, and m and n are both integers.
[0011] Preferably, in Formula 1, the anion R having the structure shown in Formula 2-1 - Total anion R - 50-100%;
[0012] Anion R having the structure shown in Formula 2-2 - Total anion R - 0~50%.
[0013] The present invention provides a method for preparing the above-mentioned natural polymer-based food packaging material, comprising the following steps:
[0014] Mixing a chitosan quaternary ammonium salt having a structure shown in Formula 3 with water to obtain a chitosan quaternary ammonium salt aqueous solution;
[0015]
[0016] In formula 3, m>0, n>0, m+n=10~600, n / m+n=0.5~0.99, m, n are both integers;
[0017] The chitosan quaternary ammonium salt aqueous solution is mixed with the sodium docusate aqueous solution and ion exchange is performed to obtain a natural polymer-based food packaging material having a structure shown in Formula 1.
[0018] Preferably, the mass concentration of the chitosan quaternary ammonium salt aqueous solution is 1-20%.
[0019] Preferably, the molecular weight of the chitosan quaternary ammonium salt is 10000 to 300000 g / mol;
[0020] The substitution degree of the chitosan quaternary ammonium salt is 50-99%.
[0021] Preferably, the mass concentration of the docusate sodium aqueous solution is 1 to 50%.
[0022] Preferably, the molar ratio of the quaternary ammonium salt functional group in the chitosan quaternary ammonium salt having the structure shown in Formula 3 to docusate sodium is 1:0.1-10.
[0023] Preferably, the ion exchange temperature is 0°C to 100°C, and the time is 0.5 to 120 hours.
[0024] Preferably, after the ion exchange, the method further comprises washing and drying the obtained ion exchange reaction liquid.
[0025] The present invention provides application of the natural polymer-based food packaging material in the field of food packaging.
[0026] The present invention provides a natural polymer-based food packaging material having a structure shown in Formula 1. Chitosan is widely distributed in nature and has high reserves. The present invention is based on a chitosan derivative-chitosan quaternary ammonium salt, and uses the anion of docusate sodium to perform ion exchange on it. On the one hand, the advantages of chitosan quaternary ammonium salt having good antibacterial properties and good film-forming properties are utilized to give the food packaging material good processing properties, and effectively solve the problem that the food packaging material is easy to breed bacteria; on the other hand, the present invention uses the anion of docusate sodium to modify the chitosan quaternary ammonium salt, and uses the anion of docusate sodium to partially or completely replace the chloride ion of the chitosan quaternary ammonium salt, which can make the food packaging material have good hydrophobicity, so that water vapor will gather on the surface of the material without infiltration, thereby having good water vapor barrier properties. The natural polymer-based food packaging material provided by the present invention has good antibacterial properties, biocompatibility, mechanical strength and water vapor barrier properties at the same time, and can be used to preserve fruits, vegetables and other foods, extend their shelf life, and reduce food waste.
[0027] The invention provides a method for preparing the natural polymer-based food packaging material. The method is based on the exchange reaction between the chloride ions of chitosan quaternary ammonium salt and the sodium ions of docusate, has simple operation, low cost and is easy to realize industrialized mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the stress-strain curve of the natural polymer-based food packaging material in Example 1;
[0029] Figure 2 The cell compatibility test results of the natural polymer-based food packaging material in Example 1;
[0030] Figure 3 These are the test results of the antibacterial properties of the natural polymer-based food packaging material of Example 3. DETAILED DESCRIPTION
[0031] The present invention provides a natural polymer-based food packaging material having a structure shown in Formula 1:
[0032]
[0033] The anion R in formula 1 - Having the structure shown in Formula 2-1 and / or Formula 2-2; in the different structural units of Formula 1, the anion R - Not all of them are structures shown in formula 2-2:
[0034]
[0035] In formula 1, m>0, n>0, m+n=10-600, n / m+n=0.5-0.99, and m and n are both integers.
[0036] In the present invention, m represents the number of repeating units of ungrafted quaternary ammonium salt in chitosan quaternary ammonium salt; m is preferably 0 to 225, more preferably 10 to 200. In the present invention, n represents the number of repeating units of grafted quaternary ammonium salt in complexed chitosan quaternary ammonium salt; m+n is preferably 100 to 600, more preferably 100 to 500. In the present invention, n / m+n is preferably 0.5 to 0.99, more preferably 0.7 to 0.99.
[0037] In the present invention, in Formula 1, the anion R having the structure shown in Formula 2-1 - Preferably, all anions R - 50 to 100%, more preferably 60 to 80%; an anion R having a structure shown in formula 2-2 - Preferably, all anions R - 0 to 50%, more preferably 20 to 40%.
[0038] The present invention provides a method for preparing the above-mentioned natural polymer-based food packaging material, comprising the following steps:
[0039] Mixing a chitosan quaternary ammonium salt having a structure shown in Formula 3 with water to obtain a chitosan quaternary ammonium salt aqueous solution;
[0040]
[0041] In formula 3, m>0, n>0, m+n=10~600, n / m+n=0.5~0.99, m, n are both integers;
[0042] The chitosan quaternary ammonium salt aqueous solution is mixed with the sodium docusate aqueous solution and ion exchange is performed to obtain a natural polymer-based food packaging material having a structure shown in Formula 1.
[0043] Unless otherwise specified, the raw materials used in the present invention are all commercially available.
[0044] The present invention mixes a chitosan quaternary ammonium salt having a structure shown in Formula 3 with water to obtain a chitosan quaternary ammonium salt aqueous solution. In the present invention, the molecular weight of the chitosan quaternary ammonium salt is preferably 10000-300000 g / mol, more preferably 50000-200000 g / mol, and further preferably 100000-150000 g / mol. In the present invention, the substitution degree of the chitosan quaternary ammonium salt is preferably 50-99%, more preferably 70%-99%.
[0045] In the present invention, the water is preferably deionized water. In the present invention, the mixing is preferably heated mixing, and the temperature of the heated mixing is preferably 45°C. In the present invention, the mass concentration of the chitosan quaternary ammonium salt aqueous solution is preferably 1-20%, more preferably 5-10%; as a specific embodiment of the present invention, the mass concentration of the chitosan quaternary ammonium salt aqueous solution is 1%, 5%, 8%, 10%, 15% or 20%.
[0046] The present invention mixes the chitosan quaternary ammonium salt aqueous solution with the docusate sodium aqueous solution and performs ion exchange to obtain a natural polymer-based food packaging material having a structure shown in Formula 1. In the present invention, the docusate sodium has a structure shown in Formula 4:
[0047]
[0048] In the present invention, the mass concentration of the docusate sodium aqueous solution is preferably 1-50%, more preferably 10-40%; as a specific embodiment of the present invention, the mass concentration of the docusate sodium aqueous solution is 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0049] In the present invention, the molar ratio of the quaternary ammonium salt functional group in the chitosan quaternary ammonium salt having the structure shown in Formula 3 to docusate sodium is preferably 1:0.1-10, more preferably 1:0.5-5, and further preferably 1:1-3.
[0050] The present invention has no special requirements for the mixing method, and any mixing method known in the art can be used, such as stirring and mixing. In the present invention, the ion exchange temperature is preferably 0 to 100°C, more preferably 20 to 60°C, and further preferably room temperature; the ion exchange time is preferably 0.5 to 120 hours, more preferably 10 to 60 hours. Chitosan quaternary ammonium salt is water-soluble, and after ion exchange with sodium docusate, the ion exchange product will precipitate from water and has good hydrophobicity.
[0051] In the present invention, after the ion exchange, the obtained ion exchange reaction liquid is preferably washed and dried. In the present invention, the washing is preferably water washing, and the drying is preferably freeze drying.
[0052] The present invention provides application of the natural polymer-based food packaging material in the field of food packaging.
[0053] The natural polymer-based food packaging material provided by the present invention, its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0054] Example 1
[0055] (1) 1.4 g of chitosan quaternary ammonium salt with a molecular weight of 100,000 g / mol and a degree of substitution of 90% and 100 g of deionized water were added to a 250 mL round-bottom flask and heated at 45° C. for 24 h until completely dissolved.
[0056] (2) Dissolve 1.9 g of the sodium docusate in 20 mL of deionized water to obtain a sodium docusate aqueous solution.
[0057] (3) The two aqueous solutions are mixed and ion exchange is performed at room temperature for 72 h (the molar ratio of the quaternary ammonium salt group to sodium docusate is 1:1). The resulting product is washed and dried multiple times to obtain a natural polymer-based food packaging material.
[0058] Example 2
[0059] (1) 1.5 g of chitosan quaternary ammonium salt with a molecular weight of 300,000 g / mol and a degree of substitution of 90% and 100 g of deionized water were added to a 250 mL round-bottom flask and heated at 45° C. for 24 h until completely dissolved.
[0060] (2) Dissolve 4.0 g of the sodium docusate in 20 mL of deionized water to obtain a sodium docusate aqueous solution.
[0061] (3) After mixing the above two aqueous solutions, ion exchange was carried out at room temperature for 72 hours (the molar ratio of quaternary ammonium salt group to sodium docusate was 1:2), and the resulting product was washed and dried multiple times to obtain a natural polymer-based food packaging material.
[0062] Example 3
[0063] (1) 1.4 g of chitosan quaternary ammonium salt with a molecular weight of 200,000 g / mol and a degree of substitution of 99% and 100 g of deionized water were added to a 250 mL round-bottom flask and heated at 45° C. for 24 h until completely dissolved.
[0064] (2) Dissolve 1.0 g of the sodium docusate in 20 mL of deionized water to obtain a sodium docusate aqueous solution.
[0065] (3) After mixing the above two aqueous solutions, ion exchange was carried out at room temperature for 72 hours (the molar ratio of quaternary ammonium salt group to sodium docusate was 1:0.6), and the resulting product was washed and dried multiple times to obtain a natural polymer-based food packaging material.
[0066] Performance Testing
[0067] (1) Tensile performance test: The natural polymer-based food packaging material obtained in the example was dissolved in DMF, and after film laying, it was placed in an oven to dry to obtain a test sample. The completely dried test sample was cut into a dumbbell-shaped specimen of 20 mm × 4 mm × 1 mm with a cutter. At least 5 dumbbell-shaped specimens were prepared for each test sample as parallel comparison. The test sample was subjected to a tensile test on a universal testing machine. The tensile rate was 10 mm / min, the test temperature was 25 ± 2 ° C, and at least 5 parallel samples were tested for each test sample.
[0068] (2) Cytotoxicity test: The test sample was cut into 3 cm × 2 cm rectangular strips, washed and dried, and then placed in 2 mL of complete culture medium for leaching at 37 °C for 24 h to obtain the extract. The CCK-8 method was used to test the cytotoxicity of the material extract. L929 cells in the logarithmic growth phase were taken and the cell count was adjusted to a cell concentration of 1 × 10 5 / mL, take 100μL and inoculate it into a 96-well plate, and culture it overnight at 37°C in a 5% CO2 constant temperature incubator to allow the cells to grow attached to the wall. Add 100μL of the extract and culture it for 24 hours, then remove the culture medium, wash it three times with sterile PBS buffer, add 100μL of 10% CCK-8 solution to each well, add 100μL of complete culture medium to the blank wells around the test well as the background group, culture it in a constant temperature incubator at 5% CO2, 37°C for 2 hours, take it out and use an enzyme reader to detect the absorbance value of each well at 450nm. The cytotoxicity of the sample was tested by calculating the cell viability. The calculation formula for cell viability is shown in Formula 1:
[0069]
[0070] (3) Antibacterial performance test: Escherichia coli and Staphylococcus aureus were used as experimental strains. First, the bacteria were inoculated into MH broth medium and cultured at 37°C for 12 h to allow the bacteria to reach the logarithmic growth phase. After centrifugation, the bacterial solution was diluted with MH broth to 5×10 5 CFU / mL is reserved. Cut the test sample into a 1.5cm×1.5cm square membrane and place it in a 6-well plate. Add 25μL of the above bacterial suspension to the center area of the membrane surface and cover it with a 1cm×1cm polyethylene (PE) film. Incubate the test sample in a constant temperature and humidity incubator at 37°C and 90% humidity for 24 hours. Then take out the test sample together with the PE cover film and place it in a 50mL sterile centrifuge tube. Add 5mL of PBS solution and vortex for 1.5min to make the bacteria adhering to the surface of the test sample fall off. Then spread the PBS solution containing bacteria on the LB agar culture, culture it overnight at 37°C, and count the number of colonies. The calculation formula for the antibacterial rate is shown in Formula 2:
[0071] Antibacterial rate (%) = (BC) / B×100 Formula 2;
[0072] In formula 2, B: average number of bacteria recovered from blank control samples;
[0073] C: Average number of bacteria recovered from antibacterial samples.
[0074] (4) Water vapor transmission rate test: The material was wrapped in a cylindrical cup containing deionized water, and the sample without the material sample wrapped in the cup was used as a blank group for control experiment. It was stored in a constant temperature and humidity chamber (37°C, 95%) for 24 hours. The mass loss of water in the cup was measured, and the calculation formula is shown in Formula 3:
[0075] X = (W1-W2) × 1000 × 24 / T Formula 3;
[0076] In formula 3, X is the water vapor transmission rate, expressed in grams per square meter per 24 hours (g·m -2 ·24h -1 );
[0077] W1: mass of container, sample and liquid, unit (g);
[0078] W2: mass of container, sample and liquid after the test period, unit (g);
[0079] T: test period, in hours (h).
[0080] The performance test results of the natural polymer-based food packaging materials obtained in Examples 1 to 3 are shown in Table 1.
[0081] Table 1 Performance test results of natural polymer-based food packaging materials obtained in Examples 1 to 3
[0082]
[0083] Among them, the stress-strain curve of the natural polymer-based food packaging material in Example 1 is as follows Figure 1 As shown, it can be seen that the tensile strength of this material is 13.8 MPa and the elongation at break is 67%.
[0084] Example 1 Cell compatibility test results of natural polymer-based food packaging materials are as follows Figure 2 As shown, Figure 2 The control group in the experiment was a cell sample to which no material extract was added.
[0085] Example 3 The antibacterial performance test results of natural polymer-based food packaging materials are as follows Figure 3 As shown. Figure 3 It can be seen that compared with the control group, the antibacterial rate of the material prepared in Example 3 against Escherichia coli is 96.0%; the antibacterial rate against Staphylococcus aureus is 99.99%.
[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A natural polymer-based food packaging material, characterized in that: It has the structure shown in formula 1: The anion R in formula 1 - Having the structure shown in Formula 2-1 and / or Formula 2-2; in the different structural units of Formula 1, the anion R - Not all of them are structures shown in formula 2-2: In formula 1, m>0, n>0, m+n=10-600, n / m+n=0.5-0.99, and m and n are both integers.
2. The natural polymer-based food packaging material according to claim 1, characterized in that: In Formula 1, the anion R having the structure shown in Formula 2-1 - Total anion R - 50-100%; Anion R having the structure shown in Formula 2-2 - Total anion R - 0~50%.
3. The method for preparing the natural polymer-based food packaging material according to claim 1 or 2, characterized in that: The following steps are involved: Mixing a chitosan quaternary ammonium salt having a structure shown in Formula 3 with water to obtain a chitosan quaternary ammonium salt aqueous solution; In formula 3, m>0, n>0, m+n=10~600, n / m+n=0.5~0.99, m, n are both integers; The chitosan quaternary ammonium salt aqueous solution is mixed with the sodium docusate aqueous solution and ion exchange is performed to obtain a natural polymer-based food packaging material having a structure shown in Formula 1.
4. The preparation method according to claim 3, characterized in that: The mass concentration of the chitosan quaternary ammonium salt aqueous solution is 1-20%.
5. The preparation method according to claim 3 or 4, characterized in that: The molecular weight of the chitosan quaternary ammonium salt is 10000-300000 g / mol; The substitution degree of the chitosan quaternary ammonium salt is 50-99%.
6. The preparation method according to claim 3, characterized in that: The mass concentration of the docusate sodium aqueous solution is 1-50%.
7. The preparation method according to claim 3, characterized in that: The molar ratio of the quaternary ammonium salt functional group in the chitosan quaternary ammonium salt having the structure shown in Formula 3 to docusate sodium is 1:0.1-10.
8. The preparation method according to claim 3, characterized in that: The ion exchange temperature is 0°C to 100°C, and the time is 0.5 to 120 hours.
9. The preparation method according to claim 3, characterized in that: After the ion exchange, the method further includes washing and drying the obtained ion exchange reaction liquid.
10. Use of the natural polymer-based food packaging material according to claim 1 or 2 or the natural polymer-based food packaging material prepared by the preparation method according to any one of claims 3 to 9 in the field of food packaging.
Citation Information
Patent Citations
Preparation method and application of hyamine cationic polyelectrolyte-anionic surfactant compound
CN104923079A
Amphipathic chitosan quaternary ammonium salt derivative and preparation and application thereof
CN106496358A
Hydrophobic polypropylene material and preparation method thereof
CN111748146A
Methods for modifying bioplymers in ionic liquids
US20070225191A1
Hyaluronic acid derivatives
US20210189018A1